Clover Leaf Drying Efficiency Using a Drying Machine with a Solar Cell - Muhandhis, Isnaini; Ni'matul Ichsan, Muchammad Ragil; Fernando, Ferdianus; Reyhan Rizqi, Muhammad; Riyanto, Ong Andre Wahyu; Ritonga, Alven Safik (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2023)
Kendung Village is known as "Kampung Semanggi" because the majority work as clover traders. The drying process of clover leaves is dried in the sun for 5 – 6 hours depending on weather conditions. During the rainy season, the drying process becomes slightly hampered due to rain or clouds. The aim of this program is to increase the efficiency of drying clover leaves by creating a drying machine powered by solar panels. This research uses the implementation method of purchasing tools and materials, making a clover leaf dryer, outreach with the local community, installing solar panels and installing batteries, testing drying time using a clover leaf drying machine. The use of a clover leaf drying machine based on solar panel electrical energy helps make the cloverleaf drying process easier, especially during the rainy season